PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN DAN BUDAYA ORGANISASI TERHADAP EMPLOYEE ENGAGEMENT KARYAWAN PERUSAHAN DAERAH AIR MINUM KOTA MALANG - Kurniawati Kurniawati; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine the effect on transformational leadership variables, organizational culture, and commitment to employee engagement Perusahaan Daerah Air Minum Kota Malang. For this reason, researchers took data from employees of the Perusahaan Daerah  Air Minum Kota Malang. This type of research is explanatory in view of the population taken from employees of the Perusahaan Daerah Air Minum Kota Malang, and the number of samples in this study was 223 employees. The acquisition of primary data is taken by distributing questionnaires to employees. the method used in this study is multiple linear regression analysis which shows that simultaneously transformational leadership variables, organizational and organizational cultures are both positively and not significantly influencing employee engagement, while partially transformational leadership variables have an insignificant positive effect on employee engagement, Organizational culture has a significant effect on employee engagement and commitment has a significant but not significant effect on employee engagement in the Perusahaan Daerah Air Minum Kota Malang. Keywords: transformational leadership, commitment, organizational culture and employee engagement